Acetaminophen intoxication is associated with decreased serum paraoxonase and arylesterase activities and increased lipid hydroperoxide levels. (November 2014) - Karadas, S; Aslan, M; Gonullu, H; Kati, C; Duran, L; Olmez, S; Kucukoglu, ME; Demir, H
Background: Acetaminophen is at present one of the most commonly used analgesics and antipyretics. Recent evidence has suggested that oxidative stress is involved in the mechanism of acetaminophen intoxication. Paraoxonase-1 (PON1) plays an important role as an endogenous free-radical scavenging molecule. The aim of this study was to evaluate the influence of serum PON1 activity and oxidative stress in patients with acetaminophen intoxication. Methods: A total of 20 patients with acetaminophen intoxication and 25 healthy controls were enrolled. Serum total antioxidant capacity (TAC), lipid hydroperoxide (LOOH) levels, and paraoxonase and arylesterase activities were measured spectrophotometrically. Results: The serum TAC levels and the paraoxonase and arylesterase activities were significantly lower in patients with acetaminophen intoxication compared with controls (all, p < 0.001), while the serum LOOH levels were significantly higher ( p < 0.001). Conclusions: Our results suggest that decreased PON1 activity seems to be associated with increased oxidative stress in patients with acetaminophen intoxication. Measuring serum PON1 activity may be useful in assessing the development of toxicity risk in acetaminophen toxicity. It would be useful to recommend vitamins with antioxidant effects such as vitamins C and E along with medical treatments.